Media Lab and Citizen Participation in Social Education: Media Lab como experiencia de innovación social y digital - Gutiérrez Pequeño, José Miguel (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
Social media labs, as spaces for experimentation, have become one of the main mechanisms of innovation today. In this framework, media labs emerge as a type of laboratory focused on experimentation with technologies and media and evolve, with the development of the digital society, towards citizen mediation and social innovation laboratories.